Nilai-nilai Pendidikan Multikultural pada Pembelajaran Pendidikan Agama Islam Jenjang Sekolah Menengah Pertama - Sujatmiko, Trisna Rizkania; Nadlif, Ainun; Astutik, Anita Puji (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to describe the results of the analysis of multicultural education values applied in the first junior high school of State 1 Gedangan Sidoarjo. The qualitative research method used in this research is descriptive. Primary data were collected directly from informants by asking questions, while secondary data were obtained from various references relevant to other scientific values from related institutions. Observation, interviews, and documentation were used as data collection strategies. Judging from the description of the results of observations and interviews with respondents, there is a sense of awareness of both teachers as educators and equal treatment of students who have social status and religious differentiation, and diverse thinking abilities. Furthermore, because the concept of multiculturalism education is recognition and mutual acceptance, tolerance, inclusion, harmony, honesty, and mutual respect for differences, the ability and understanding of teachers about multicultural education in Islamic religious education learning at SMP Negeri 1 Gedangan is the key to the success of planting multicultural values in Islamic religious education learning. The results of the study state that the application of multicultural values has gone well. After receiving an understanding of multicultural education, students have a sense of mutual respect for differences. This can be seen from the daily attitudes and behaviors of students who respect each other and never question their differences.